Intervensi Kesehatan Masyarakat dalam Pencegahan Hipertensi dan Diabetes di RT 24 Padukuhan Wonocatur, Kalurahan Banguntapan - Tri Wahyuni Sukesi; Berlianty Ratu Piningit; Tri Septi Nabila; Nindya Patricia; Firda Meila Isnaini; Aulia Lintang Priyanta; Raina Amalia Putri; Elysanti Toring Elma Bura (CV. Rayyan Dwi Bharata, 2026)
This study aimed to identify priority health problems and implement community-based health interventions to prevent hypertension and diabetes in RT 24 Wonocatur, Banguntapan. The activity was conducted using a Problem Based Learning (PBL) approach through observation, interviews, questionnaires, and community discussions. Data analysis was carried out by identifying health problems and determining priorities using the USGF method. The results showed that hypertension and diabetes were the main health problems faced by the community. Interventions were implemented in the form of health screenings, including blood pressure and blood glucose examinations, health education, and group exercise activities. The intervention increased community awareness of the importance of early detection and regular physical activity as preventive efforts against hypertension and diabetes. Community participation played an important role in supporting the implementation of health promotion and prevention activities at the neighborhood level.